Fabrication of Fe3O4@PVA-Cu Nanocomposite and Its Application for Facile and Selective Oxidation of Alcohols - Rahimi, Jamal; Niksefat, Maryam; Maleki, Ali (Frontiers in Chemistry, 2020)
Fe3O4@PVA-Cu nanocomposite was introduced as an affordable catalyst for selective oxidation of alcohols into various aldehydes and ketones. The synthesized nanocomposite was characterized by applying essential analyses. The peaks that are appeared in FT-IR spectroscopy confirmed the production of the Fe3O4@PVA-Cu nanocomposite. In addition, EDX analysis proved the presence of oxygen, carbon, iron, and copper elements in the catalyst. Further, TGA analysis showed high thermal stability of the nanocomposite. VSM technique was applied to examine the magnetic property of the nanocomposite. The results demonstrated a high magnetic property in the catalyst, which enables easy separation of it from the reaction solution. TEM and SEM imaging showed the nanoscale size of the particles (~20 nm) in the catalyst. Additionally, XRD data was compatible with that of Fe3O4 nanoparticles. The application of the nanocomposite has been studied in the selective oxidation of alcohols in the presence of acetonitrile as solvent, and hydrogen peroxide as a supplementary oxidizing agent. This technique is remarkably facile and inexpensive. Further, the products showed high yields. In addition, the calculated TON and TOF values indicated the phenomenal efficiency of the nanocomposite in preparation of targeted products.